Relavansi Pemikiran Pendidikan Cokroaminoto Dengan Anis Baswedan - Edi sumanto (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2016)
Abstract : The journal wants to find the relevance of educational thought Clark Aminotowith Anis Baswedan because it includes people who care about education. Nationaleducation desired by H.O.S. Tjokroaminoto is patriotism that is desperately conducteducation to instill a feeling of nationality; have the courage always to instill a sense ofcourage, especially jihad